Pesticide exposure assessment for surface waters in the EU. Part 2: Determination of statistically based run‐off and drainage scenarios for Germany. Issue 5 (1st February 2017) - Bach, Martin; Diesner, Mirjam; Großmann, Dietlinde; Guerniche, Djamal; Hommen, Udo; Klein, Michael; Kubiak, Roland; Müller, Alexandra; Preuss, Thomas G; Priegnitz, Jan; Reichenberger, Stefan; Thomas, Kai; et al.
Abstract: BACKGROUND: In order to assess surface water exposure to active substances of plant protection products (PPPs) in the European Union (EU), the FOCUS (FOrum for the Co‐ordination of pesticide fate models and their USe) surface water workgroup introduced four run‐off and six drainage scenarios for Step 3 of the tiered FOCUSsw approach. These scenarios may not necessarily represent realistic worst‐case situations for the different Member States of the EU. Hence, the suitability of the scenarios for risk assessment in the national authorisation procedures is not known. RESULTS: Using Germany as an example, the paper illustrates how national soil–climate scenarios can be developed to model entries of active substances into surface waters from run‐off and erosion (using the model PRZM) and from drainage (using the model MACRO). In the authorisation procedure for PPPs on Member State level, such soil–climate scenarios can be used to determine exposure endpoints with a defined overall percentile. CONCLUSION: The approach allows the development of national specific soil–climate scenarios and to calculate percentile‐based exposure endpoints. The scenarios have been integrated into a software tool analogous to FOCUS‐SWASH which can be used in the future to assess surface water exposure in authorisation procedures of PPPs in Germany. © 2017 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.